A 15-year follow-up of former self-harming inpatients in child & adolescent psychiatry – a qualitative study. (1st May 2020) - Hansson, Kristian; Malmkvist, Lars; Johansson, Björn Axel
Abstract: Purpose: Self-harm is common among adolescents, and is even more frequent among psychiatric populations. The aim of this study was to increase knowledge and understanding of different aspects of life for adults who, when adolescents, had engaged in severe self-harm during inpatient stays. Material and methods: Individual semi-structured interviews were held with seven former inpatients with a history of severe self-harm during inpatient stay in their adolescence. The interviews were analysed using a qualitative method, and the results were described in the form of categories and sub-categories. Results: Five categories, with 16 sub-categories, were found to be related to the former patients' experiences of their lives. At the time of the interviews, the subjects were in their early thirties and had no ongoing self-harm. In childhood they had experienced a dysfunctional relationship with one or both of their parents, and self-harm was one of several destructive behaviours. Friendships outside the unit were difficult during adolescence. Soon after admission to the psychiatric inpatient unit, relationships with other patients became important and contributed to them wanting to stay at the unit. Meaningful relationships and being part of a social context with healthy expectations were seen as important factors for stopping self-harm at a later stage. The subjects' experiences of their life today ranged from not enjoying it to accepting their current situation. Conclusion: These findings are based on a small sample, but they indicate the importance of relationships and the social context in contributing to and then ending self-harm.